Primary cilia and hypoxia-associated signaling in developmental odontogenic cysts in relation to autosomal dominant polycystic kidney disease - A novel insight - Szaraz, David; Danek, Zdenek; Lipovy, Bretislav; Krivanek, Jan; Buchtova, Marcela; Moldovan Putnova, Barbora; Putnova, Iveta; Stembirek, Jan; Andrasina, Tomas; Divacka, Petra; Izakovicova Holla, Lydie; Borilova Linhartova, Petra (Heliyon, 2023)
Developmental cysts are pathological epithelial-lined cavities arising in various organs as a result of systemic or hereditary diseases. Molecular mechanisms involved in the formation of developmental odontogenic cysts (OCs) are not fully understood yet; the cystogenesis of renal cysts originating from the autosomal dominant polycystic kidney disease (ADPKD) has been, however, explored in much greater detail. This narrative review aimed i) to summarize molecular and cellular processes involved in the formation and growth of developmental OCs, especially dentigerous cysts (DCs) and odontogenic keratocysts (OKCs), ii) to find if there are any similarities in their cystogenesis to ADPKD cysts, and, based on that, iii) to suggest potential factors, candidate molecules, and mechanisms that could be involved in the DC formation, thus proposing further research directions. Here we suggest a possible association of developmental OCs with primary cilia disruption and with hypoxia, which have been previously linked with cyst formation in ADPKD patients. This is illustrated on the imagery of tissues from an ADPKD patient (renal cyst) and from developmental OCs, supporting the similarities in cell proliferation, apoptosis, and primary cilia distribution in DC/OKC/ADPKD tissues. Based on all that, we propose a novel hypothesis of OCs formation suggesting a crucial role of mutations associated with the signaling pathways of primary cilia (in particular, Sonic Hedgehog). These can lead to excessive proliferation and formation of cell agglomerates, which is followed by hypoxia-driven apoptosis in the centers of such agglomerates (controlled by molecules such as Hypoxia-inducible factor-1 alpha), leading to cavity formation and, finally, the OCs development. Based on this, we propose future perspectives in the investigation of OC pathogenesis.
Keywords: Polycystin; Primary cilia; Sonic hedgehog pathway; Dentigerous cyst; Odontogenic keratocyst; Polycystic kidney disease; Developmental odontogenic cyst